Modelling and Simulation of a Sensorless Control of a True Asymmetric Cascade H-Bridge Multilevel Inverter PMSM Drives - Kamel Saleh; Mark Sumner (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper introduces a new method to track the saliency of an AC motor fed by a multilevel converter through measuring the dynamic current response of the motor line currents due the IGBT switching actions. The method uses only the fundamental PWM waveform (i.e there is no modification to the operation of the multilevel converter) similar to the fundamental PWM method proposed for a 2-level converter. Simulation results are provided to demonstrate the performance of the complete sensorless speed control of a PM motor driven by such a converter over a wide speed range. Finally the paper introduces a comparison between the 2-level converter and the multilevel converter in terms of the reduction of the Total Harmonic Distortion (THD) using the fundamental PWM method in both cases.